Job Autonomy, Organizational Learning, and Work Environment on Organizational Commitment - Desvianti Rahmadani; Rini Sarianti (Universitas Negeri Padang, 2022)
This poprpuse of this reserch is to analyze the effect of job autonomy, organizational learning, and work environmnet commitment of PT PLN (Persero) UP3 Padang. Data was collected using questionnaires to 74 employees of PT PLN (Persero) UP3 Padang. The data that has been collected is then processed using SPSS. The results showed that job autonomy had a positive but not significant effect on organizational commitment. Further findings organizational learning has a positive and significant effect on organizational commitment, lastly the work environment has a positive and significant effect on organizational commitment.